Strategi Kebijakan Pengembangan Pendidikan Agama dalam Mendukung Pembangunan Wilayah Perbatasan di Provinsi Kalimantan Utara - Rachmansyah, Arie Nova (JURNAL ILMIAH GEMA PERENCANA, 2024)
This Policy Paper describes that the border areas in North Kalimantan have unique characteristics, in terms of geography, society, culture, and economy. Religious education in this area has a very important role in shaping the character of the community, strengthening national values, and supporting regional development. However, there are several challenges faced in the development of religious education in border areas, such as limited access to educational facilities, lack of qualified teachers, and the influence of foreign cultures. Therefore, religious education can be a catalyst in building a harmonious, tolerant, and competitive society. This paper analyzes the contribution of religious education to the development of border areas and formulates policy strategies that can strengthen the role of religious education in achieving development goals. This article uses a qualitative method that focuses on understanding the meaning and interpretation of social phenomena in border areas, with a descriptive-analytical approach to describe and analyze data in detail and in-depth. The results show that quality religious education can improve the quality of human resources, strengthen national values, and support regional economic development. Moreover, the management of the border area in North Kalimantan which directly borders Malaysia. Due to its proximity, there is significant cross-border interaction and activity among the people living in this area, especially the people in Malinau and Nunukan Regencies. So the role of religious education becomes a strategic significance in the formation of character and the face of the people in this inter-country region.